OsHemA gene, encoding glutamyl-tRNA reductase (GluTR) is essential for chlorophyll biosynthesis in rice (Oryza sativa) - Zhao-qiong ZENG; Tian-zi LIN; Jie-yu ZHAO; Tian-hui ZHENG; Le-feng XU; Yi-hua WANG; Ling-long LIU; Ling JIANG; Sai-hua CHEN; Jian-min WAN (Journal of Integrative Agriculture)
Chlorophyll (Chl) biosynthesis is essential for photosynthesis and plant growth. Glutamyl-tRNA reductase (GluTR) catalyzes glutamyl-tRNA into glutamate-1-semialdehyde (GSA) and initiates the chlorophyll biosynthesis. Even though the main role of GluTR has been established, the effects caused by natural variations in its corresponding gene remain largely unknown. Here, we characterized a spontaneous mutant in paddy field with Chl biosynthesis deficiency, designated as cbd1. With intact thylakoid lamellar structure, the cbd1 plant showed light green leaves and reduced Chl and carotenoids (Cars) content significantly compared to the wild type. By map-based gene cloning, the mutation was restricted within a 57-kb region on chromosome 10, in which an mPingA miniature inverted-repeat transposable element (MITE) inserted in the promoter region of OsHemA gene. Both leaf color and the pigment contents in cbd1 were recovered in a complementation test, confirming OsHemA was responsible for the mutant phenotype. OsHemA was uniquely predicted to encode GluTR and its expression level was dramatically repressed in cbd1. Transient transformation in protoplasts demonstrated that GluTR localized in chloroplasts and a signal peptide exists in its N-terminus. A majority of Chl biosynthesis genes, except for POR and CHLG, were down-regulated synchronously by the repression of OsHemA, suggesting that an attenuation occurred in the Chl biosynthesis pathway. Interestingly, we found major agronomic traits involved in rice yield were statistically unaffected, except for the number of full grains per panicle was increased in cbd1. Collectively, OsHemA plays an essential role in Chl biosynthesis in rice and its weak allele can adjust leaf color and Chls content without compromise to rice yield.